2014
DOI: 10.1021/cs5016029
|View full text |Cite
|
Sign up to set email alerts
|

Living Polymerization of Ethylene and Copolymerization of Ethylene/Methyl Acrylate Using “Sandwich” Diimine Palladium Catalysts

Abstract: Cationic Pd(II) catalysts incorporating bulky (8-p-tolylnaphthyl) substituted diimine ligands have been synthesized and investigated for ethylene polymerization and ethylene/methyl acrylate copolymerization. Homopolymerization of ethylene at room temperature resulted in branched polyethylene with narrow M w /M n values (ca. 1.1), indicative of a living polymerization. A mechanistic study revealed that the catalyst resting state was an alkyl olefin complex and that the turnover-limiting step was migratory inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
158
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(162 citation statements)
references
References 42 publications
2
158
2
Order By: Relevance
“…Recently, Brookhart et al [58] reported living polymerization of ethylene at room temperature using "sandwich" -diimine palladium complexes 7a and 7b. This was also attributed to the increased axial steric bulkiness provided by the capping arene groups.…”
Section: Ligand Designmentioning
confidence: 99%
“…Recently, Brookhart et al [58] reported living polymerization of ethylene at room temperature using "sandwich" -diimine palladium complexes 7a and 7b. This was also attributed to the increased axial steric bulkiness provided by the capping arene groups.…”
Section: Ligand Designmentioning
confidence: 99%
“…Subsequently, ligands L1-L3 were obtained in 39-47% yields from the reaction of 1 equivalent of n BuLi with the lithium salt in THF (tetrahydrofuran) followed by the addition of R2PCl. These ligands were characterized by by 1 H, 13 C, and 31 The reactions of ligands L1-L3 with (TMEDA)PdMe2 (TMEDA = tetramethylethylenediamine) in DMSO (dimethylsulfoxide) led to the formation of the Pd(II) complexes (Pd1-Pd3) at 41-48% yields (Scheme 2). The reaction of ligands L1-L3 with Na2CO3 and trans-[(PPh3)2Ni(Cl)Ph] afforded the desired Ni(II) complexes (Ni1-Ni3) at 34-76% yields.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction of ligands L1-L3 with Na2CO3 and trans-[(PPh3)2Ni(Cl)Ph] afforded the desired Ni(II) complexes (Ni1-Ni3) at 34-76% yields. These metal complexes were characterized using 1 H, 13 C, and 31 P NMR (see Supplementary Materials, Figures S10-S20), elemental analysis and MALDI-TOF-MS (Matrix Assisted Laser Desorption Ionization-Time of Flight-Mass Spectrometry). For comparison purpose, the palladium complex Pd2′/Pd2″ and the nickel complex Ni2′/Ni1″ were prepared according to literature procedures [48,49].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These tailored cyclic olefin copolymers bear the potential for functionalization through polymer-analogous reactions at the double bonds present in the copolymers. [10][11][12][13][14] In terms of polymer synthesis, the ligand system at the group 4 metals as such was designed in a way that it can switch from VIP to ROMP via abstraction of the α-proton from the growing polymer chain by the nitrogen at the pyrid-2-yl moiety. [10][11][12][13][14] In terms of polymer synthesis, the ligand system at the group 4 metals as such was designed in a way that it can switch from VIP to ROMP via abstraction of the α-proton from the growing polymer chain by the nitrogen at the pyrid-2-yl moiety.…”
Section: Introductionmentioning
confidence: 99%